2021
DOI: 10.3390/pharmaceutics13050677
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Therapeutic Efficacy of Thymoquinone-Loaded Liposomes against Drug-Sensitive and Drug-Resistant Acinetobacter baumannii

Abstract: In the present study, we investigated the activity of free thymoquinone (TQ) or liposomal thymoquinone (Lip-TQ) in comparison to standard antibiotic amoxicillin (AMX) against the drug-sensitive and drug-resistant Acinetobacter baumannii. A liposomal formulation of TQ was prepared and characterized and its toxicity was evaluated by analyzing the hematological, liver and kidney function parameters. TQ was effective against both drug-sensitive and drug-resistant A. baumannii as shown by the findings of drug susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Despite possessing a wide range of therapeutic properties, the clinical use of TQ has been restricted owing to its meager solubility and bioavailability. The incorporation of TQ in various drug delivery systems has augmented the therapeutic efficacy of the drug [14,16]. The results of the present study demonstrated greater activity of TQ in lipid nanoparticle formulation because A. baumannii-infected leukopenic mice treated with Lip-TQ (10 mg/kg) had a 60% survival rate on day 40 post-infection, whereas the mice in the group treated with free TQ at the same dose died before day 40 post-infection.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Despite possessing a wide range of therapeutic properties, the clinical use of TQ has been restricted owing to its meager solubility and bioavailability. The incorporation of TQ in various drug delivery systems has augmented the therapeutic efficacy of the drug [14,16]. The results of the present study demonstrated greater activity of TQ in lipid nanoparticle formulation because A. baumannii-infected leukopenic mice treated with Lip-TQ (10 mg/kg) had a 60% survival rate on day 40 post-infection, whereas the mice in the group treated with free TQ at the same dose died before day 40 post-infection.…”
Section: Discussionmentioning
confidence: 63%
“…The liposomal formulation of TQ was prepared and characterized as described earlier [16]. All the constituents, including PC, Chol, and TQ, were dissolved in a methanol and chloroform mixture (1:1 Vol/Vol) in a round-bottom flask.…”
Section: Formulation Of Tq-loaded Lipid Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their specific structural and technological modifications reducing toxicity are possible. For example, liposomal encapsulation of thymoquinone was found to be effective in decreasing its toxic effects [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 − A Free antigen /A Total antigen (1) where A Free antigen is the amount of antigen present in the supernatant; A Total antigen is the amount of total antigen initially added. The size and shape of the DRVs were determined by transmission electron microscopy (TEM), whereas the polydispersity index (PDI) and zeta potential were revealed by the Malvern Nano Zeta Sizer (Malvern Instruments, Southborough, MA, USA), using the dynamic light scattering (DLS) technique as previously described [22].…”
Section: Preparation and Characterization Of Drvsmentioning
confidence: 99%